تأثير تدريبات القوة الوظيفية في تطوير بعض القدرات البدنية والتهديف بكرة القدم - عاشور, امساعيل عبدزيد; حسن, محمد غني; خطيب, علي خوام (Sulaimani Journal for Humanities, 2018)
The message included a five door, touched a researcher at the door to the first, which made clear the importance of research in the use of force functional exercises designed to develop some physical abilities and scoring football. The study aimed to: - Prepare a training curriculum for functional strength for the development of physical capacities and capabilities that suit the research sample. - Understand the impact of a program of functional strength in the development of some physical abilities and scoring football. - There are significant differences between the tests before and after the sample in some physical abilities and scoring football for the control and experimental groups. - There are significant differences between the a posteriori tests of the control and experimental groups in certain physical capacities and in favor of the experimental group. And included the area of human players Karkh Sports Club (youth category) as the experiment conducted for the period from 1/2/2017 until 28/3/2017 in the Sports Hall in the Karkh district of Baghdad. In Part II dealt with the researcher to the two main axes, which touched on the theoretical side to force the functional and physical capacity and to basic skills in football and the second axis of previous studies, which included three studies of the local environment and Arabic. In Part III radicalized the researcher to the research methodology and procedures used if the curriculum included Altgerabive research and tools and equipment used, and the most important tests of physical skill, and also explained the statistical methods. In Part V, which included the conclusions of which were the most important: • the emergence of statistically significant differences in the tests before and after the experimental group in some physical Akaddarat. • differing rates of development of the experimental group in the skill of the accuracy of scoring football. • differing rates of development of the experimental group in the skill of the accuracy of scoring football. • Oamah emphasis on muscle strength and functional strength training into the training curricula used in the sport of gymnastics. • the need to conduct periodic tests of physical capacity and scoring at the level of football players Karkh Club.